Holistic construction project management - Hamimah Adnan (Penerbit Universiti Teknologi Mara, 2012)
As the title indicates, a holistic perspective of management is presented in this book to allow community of professionals and students alike to gain and enhance their knowledge as well as performance in management systems of construction projects.